A Jewish tax with a Latin name the "aurum coronarium" - Appelbaum, Alan 1936- (2025)
The tax collected by the Jewish Patriarch in late antiquity has no name in Jewish sources, but in one instance Roman law calls it by the same name as a particular Roman tax. Building on the work of Clifford Ando, this note discusses what the two taxes had in common, and proposes that the Jewish tax played an important role in bringing about the idea of a single Jewish people rather than various groups of people of Jewish ancestry living in various communities.
Keywords: Jewish Patriarch; Judea; Late Antiquity; Roman Empire; Diaspora; Tax; Terminology